The situation as regards diabetes mellitus type 1 in Andalusia. Care data, use of advanced therapies and human resources - Juan Pedro López-Siguero; Olga Pérez-González; Ana Lucía Gómez-Gila; Isabel Leiva-Gea (Elsevier, 2018)
Introduction: The representation of Spain in European epidemiological studies on diabetes is limited, with only one centre in the Hvidoere study and another in the SWEET study. No Spanish studies have been published that combine epidemiological data and care resources. The aim of this study was to determine the epidemiological data, care resources and use of new technologies in all Andalusian hospitals that care for children with diabetes mellitus type 1 (DM1) under 14 years. Material and methods: An electronic questionnaire of 18 questions was sent to all paediatric endocrinologists who treated children with diabetes in Andalusian hospitals. Results: There was a mean of 3.12 (SD: 2.58) paediatric endocrinologist for every 100 patients, with a mean diabetes nurse educator ratio of 2.50 (SD: 3.94) per 100 patients and centre. Only 1 of the 29 centres had a psychologist, 9/29 had a day hospital and 11/29 had a 24-h telephone line. The mean of days of consultations exclusively for patients with DM1 was 1.56 days (SD: 1.21) per week. Continuous insulin infusion was used to treat 5% of patients, with a significant increase in centres with more than 150 patients. Conclusions: This study offers, for the first time, current data on the epidemiological situation related to healthcare data, comparing them with the recommendations of European standards, highlighting a low ratio of endocrinologists and educators in diabetes, absence of psychologists and low technology penetrance. Resumen: Introducción: La representación de nuestro país en los estudios epidemiológicos europeos en diabetes es exigua, tan solo un centro en el estudio Hvidoere y otro en el SWEET. No existen estudios publicados en España que combinen datos epidemiológicos y recursos asistenciales. El objetivo de este estudio es conocer los datos epidemiológicos, los recursos asistenciales y el uso de nuevas tecnologías en los hospitales andaluces que atienden a niños con diabetes mellitus tipo 1 (DM1) menores de 14 años. Material y métodos: Un cuestionario electrónico de 18 preguntas fue enviado a los endocrinólogos pediátricos que atendían a niños con DM1 en todos los hospitales andaluces. Resultados: La media de la ratio de endocrinólogo pediátrico por 100 pacientes fue 3,12 (DE: 2,58). La media de la ratio de enfermero educador en diabetes por 100 pacientes y centro fue de 2,50 (DE: 3,94). Solo uno de los 29 centros disponía de psicólogo, 9/29 disponían de hospital de día y 11/29 disponían de atención telefónica durante 24 h. La media de días de consulta a la semana destinados exclusivamente a pacientes con DM1 fue de 1,56 días (DE: 1,21). Un 5% de los pacientes fueron tratados con infusor continuo de insulina, con un aumento significativo en los centros que tenían más de 150 pacientes. Conclusiones: Este estudio ofrece por primera vez datos actuales de la situación epidemiológica en Andalucía en relación con los datos asistenciales; comparándolos con las recomendaciones de estándares europeos, destaca una baja ratio de endocrinólogos y educadores en diabetes, ausencia de psicólogo y baja penetrancia de tecnología.